Effect of 2-Day Very Low-Calorie Diet on Perceived Stress, Cognitive Functions and Mood in Overweight and Obese Men (Baltic Journal of Sport and Health Sciences, 2017)
Background. It is well established that intermittent long-term fasting, during which a very low-calorie diet is allowed 2-days a week, improves weight loss, mood and cognitive functions. However, we are not aware of any previous studies on the effect of a 2-day very low-calorie diet on brain functioning. Thus, the purpose of this study was to determine the effect of 2-day very low-calorie diet on perceived stress, cognitive functions and mood in overweight and obese men.Methods. Nine young adult men (body mass index (BMI) from 26.7 to 32.1 kg/m 2 ) completed a 2-days very low-calorie diet (536 kcal) and 2-day usual diet program in a randomized order. Perceived stress (subjective stress rating and cardiovascular response), cognitive performance, and mood were evaluated before and after both diets.Results. A subjective stress rating in relation to the very low-calorie diet condition was 37.4 ± 18.7. There were no detectable effects of acute calorie restriction on cardiovascular response (heart rate and blood pressure) and on any aspect of cognitive performance. Meanwhile, sense of vigor increased (p < .05) and negatively correlated with BMI (r = −.780, p < .05).Conclusions. The two-day very low-calorie diet evoked a mild stress, which did not affect sympathetic nervous system  response  and  cognitive  performance  in  overweight  and  obese  men.  Furthermore,  very  low-calorie  diet increased vigor, which was strongly associated with decreased body mass index.Keywords:  adiposity, cognitive performance, body mass index, fasting, heart rate.